Amygdalectomy and disconnection in visual learning for auditory secondary reinforcement by monkeys. - Gaffan, D; Harrison, S (1987)
Nine monkeys in 3 groups took part in an experiment on visual discrimination learning set in an automatic apparatus. Each new visual discrimination problem was solved using auditory secondary reinforcers. Primary food reinforcement was delivered only after a new problem had been solved to a criterion, and the problem was then replaced by a new one; thus, within-problem learning relied purely on secondary and not on primary reinforcement, but the secondary reinforcers were associated with primary reinforcement. Bilateral amygdalectomy severely retarded within-problem learning. Disconnection of the amygdala from auditory input, by crossed unilateral lesions of amygdala and of auditory cortex combined with forebrain commissurotomy, had a similar effect to that of bilateral amygdalectomy. Disconnection of the amygdala from visual association cortex left learning unimpaired. Thus, for normal performance in this task, interaction of the amygdala with the sensory modality of the secondary reinforcer was essential, but interaction of the amygdala with the sensory modality of the discriminative stimuli was not necessary. It was concluded that the amygdala is involved in associating stimuli with the primary reinforcing attributes of food reward, and not with its other attributes.